Prenatal Diagnosis and Outcome of Fetuses with Double-Inlet Left Ventricle - Gidvani, Monisha; Ramin, Kirk; Gessford, Ellen; Aguilera, Marijo; Giacobbe, Lauren; Sivanandam, Shanthi (American Journal of Perinatology Reports, 2011)
The aim of this study is to characterize the in utero presentation of the subtype of double-inlet left ventricle (DILV), a rare congenital heart disease, and assess the postnatal outcome. We retrospectively studied fetuses diagnosed prenatally with DILV between 2007 and 2011. We reviewed the prenatal and postnatal echocardiograms, clinical presentations, karyotypes, and the postnatal outcomes. There were eight fetuses diagnosed with DILV with L-transposition of the great vessels (S, L, L). Mean gestational age at diagnosis was 24.7 weeks. Of these, four fetuses (50%) had pulmonary atresia. One fetus (12.5%) also had tricuspid atresia and coarctation of the aorta and died at 17 months of age. Complete heart block and long QT syndrome was present in one fetus (12.5%), who died shortly after birth. There were no extracardiac or karyotypic abnormalities. Six (75%) infants are alive and doing well. Double-inlet left ventricle with varied presentation can be accurately diagnosed prenatally. The outcome of fetuses is good in the absence of associated rhythm abnormalities with surgically staged procedures leading to a Fontan circulation.
Keywords: Congenital heart disease; double-inlet left ventricle; fetal echocardiography; single ventricle